2018
DOI: 10.2174/1874210601812010219
|View full text |Cite
|
Sign up to set email alerts
|

Fem and Von Mises Analysis of OSSTEM ® Dental Implant Structural Components: Evaluation of Different Direction Dynamic Loads

Abstract: Purpose:The objective of this investigation is to study prosthodontics and internal components resistance to the masticatory stress and considering different force directions by using Finite Element Method analysis (FEM). The structural materials of the components are usually Titanium alloy grade 4 or 5 and thus, guarantee the integration of the fixture in the bone due to the osteointegration phenomena. Even if the long-term dental implant survival rate is easy to be obtained and confirmed by numerous research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
75
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 88 publications
(76 citation statements)
references
References 24 publications
0
75
0
1
Order By: Relevance
“…In this specific study, the authors obtained a balance for achieving outcomes that are as similar to reality. 9,[18][19][20][21][22][23] A CAD drawing of each element has been developed and then assembled in a unique model with relative adaption. At the same time, the purpose of the investigation is to research the global tension on the four groups.…”
Section: Resultsmentioning
confidence: 99%
“…In this specific study, the authors obtained a balance for achieving outcomes that are as similar to reality. 9,[18][19][20][21][22][23] A CAD drawing of each element has been developed and then assembled in a unique model with relative adaption. At the same time, the purpose of the investigation is to research the global tension on the four groups.…”
Section: Resultsmentioning
confidence: 99%
“…16 The level of stress in the cortical bone was much higher than that in the cancellous bone, mainly reflecting the difference in Young's modulus, as mentioned in other studies. 17,18 Several finite element studies have reported a reduction in the crestal bone strain by increasing the implant diameter. 8,13,[19][20][21] Also, it has been stated that the implant diameter is more important than its length in improving the stress distribution pattern.…”
Section: Discussionmentioning
confidence: 99%
“…[27][28][29]. These simulations could be performed by discretizing a real system and performing a finite element simulation [30][31][32]. Glass fiber finds its primary application as a reinforcement for long-term temporary crowns, for the temporary Toronto Bridge or the Maryland bridge, and for bridges on inlays.…”
Section: Discussionmentioning
confidence: 99%